Comparative Proximate Composition and Hypoglycemic Properties of Three Medicinal Plants (Verononia amygdalina, Azadirachta indica and Moringa oleifera). - Okey, Ojiako A.; C, Chikezie; Chidoka, Paul (Pharmacognosy Communications)
The present study sought to investigate proximate composition in relation to the short and long term hypoglycemic effects of ethanol/water leaf extracts of Verononia amygdalina, Azadirachta indica and Moringa oleifera on hyperglycemic rats. Hyperglycemia was induced by a single intra-peritoneal injection of 0.1 mol/L alloxan monohydrate in phosphate buffer saline (PBS) solution (pH =7.4) dosage = 140 mg/kg; b/w. Individual hyperglycemic rats received separate doses of either 400 mg/kg bw/12 h of V. amygdalina, A. indica or M. oleifera for 14 days. Blood samples were drawn from the rats at regular intervals of 12 h for 48h duration; for short-term study, and subsequently, on days 3, 7, 10 and 14; for long term study, and measured for fasting blood glucose (FBG). Determination of FBG was by the glucose oxidase method. V. amygdalina, A. indica and M. oleifera showed wide variation in crude protein content (CPC), which was within the range of 13.42–37.01%. Total carbohydrate content (TCC) of V. amygdalina and A. indica was the single highest component with values: TCCV. amygdalina = 40.65% and TCCA. indica = 50.14%. In contrast, the CPC content was higher than theTCC contentfor M. oleifera (TCCM. oleifera = 36.65%; CPCM. oleifera = 37.01%). The administration of V. amygdalina, A. indica and M. oleifera to the rats (0 h “ t “ 48 h) did not cause significant (p > 0.05) reduction in FBG of hyperglycemic rats compared to the control group. Conversely, the administration of the three leaf extracts caused reduction in FBG in a time dependent manner in the order: H[M. oleifera] = 400 mg/kg; bw = 2.73 folds >H[V. amygdalina] = 400 mg/kg; bw = 2.15 folds >H[A. indica] = 400 mg/kg; bw = 1.75 folds; p < 0.05. Comparative proximate composition of V. amygdalina, A. indica and M. oleifera and corresponding capacity of the three leaf extracts to reduce FBG appears to suggest that biomolecules responsible for promoting FBG lowering effects are for the most part the TCC and CPC elements.
Keywords: Proximate composition; fasting blood glucose; Verononia amygdalina; Azadirachta indica and Moringa oleifera